ASSESSMENT OF THE LEVEL OF HEAVY METAL CONCENTRATION IN THE STREET DUST IN SOME SELECTED LOCATIONS IN ZARIA METROPOLIS, KADUNA STATE, NIGERIA - Nimyel, Suleman H.; Namadi, M. M. (FUDMA JOURNAL OF SCIENCES, 2020)
The study investigate the level of heavy metal concentration in street dust in some selected locations in Zaria metropolis, by monitoring the concentration of Chromium (Cr), Cadmium (Cd), Nickel (Ni), Lead (Pb), and Copper (Cu) for eight weeks. Street dust samples were collected by placing polyethylene bags on randomly selected roof tops and road sides at 20 cm to 30 cm to form composite sample. Sample collected were pre-treated and digested using standard procedure. Atomic Absorption Spectrophotometer (AAS) was used to determine the concentration of heavy metals. Results obtained showed that the concentration of Cr range from 16.670 ±2.20 μg/g to 31.895 ±1.845 μg/g, Cd concentration range from 0.280 ±0.042 μg/g to 1.900 ± 1.202 μg/g, Ni concentration range from 1.560 ±0.254 μg/g to 5.880 ±1.173 μg/g, Pb concentration range from 22.290 ±2.248 μg/g to 95.485 ±3.019 μg/g, Cu concentration range from 0.225 ±0.063 μg/g to 1.280 ±0.353 μg/g. The concentration of all heavy metals are below the limit set be World Health Organization (WHO) and therefore do not pose any health risk to humans. In sampled areas, the main sources of these heavy metals were anthropogenic activities such as open waste incineration, vehicle traffic, and ongoing construction at certain locations.